7.22 ЧЕТ ЭЛ ФУҚАРОЛАРИ ТОМОНИЛАН ЁКИ УЛАР ИШТИРОКИДА СОДИР ЭТИЛГАН ЖИНОЯТЛАРНИ ТЕРГОВ ҚИЛИШНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ - Абдуллаев Ориф Қосим ўғли, Ўзбекистон Республикаси Ҳуқуқни муҳофаза қилиш Академияси магистранти (Innovative technologies in construction Scientific Journal, 2024)
The article considers the periodicity of defectoscopic diagnostics of rail condition. Key words: Rail, trackless track, rail defects, rail stresses. Currently, to establish the periodicity of defectoscopic diagnostics of rail condition on the track, mainly expert methods are used, based on the results of laboratory studies, operational observations or estimates related to individual experimental sections. To the greatest extent these questions were worked out in 1986 by a group of scientists of VNIIJT [1]. However, the results of this work according to [2] were not adapted for application, because they did not take into account the actual rail yield at specific track sections, and when determining the number of defectoscopic diagnostics, a stock factor equal to three was used, which could not provide optimization of the system of such defectoscopic diagnostics of rail condition in the track. The current technology of defectoscopic diagnostics of rails in the track is based on a series of defectoscopic diagnostics, the purpose of which is to detect a dangerous defect before the onset of its fracture. And detection of a defect is preceded, as a rule, by several empty defectoscopic diagnostics. Thus, according to [2] in 2000 one acutely defective rail, detected by removable diagnostics. This is due to the fact that a part of such defectoscopic diagnostics is carried out in the period when the defect has not yet originated or the degree of its development does not allow detecting damage in the metal during specific defectoscopic diagnostics. To determine the number of such defectoscopic diagnostics in different operating conditions, it is necessary to establish a number of dependencies according to [2]. As the number of such defectoscopic diagnostics in a cycle is influenced by many factors, its duration of phenomena is a random value, in connection with what according to [2] it is necessary to find the law of its distribution, and, moreover, for normalization of number of such defectoscopic diagnostics on a concrete section of a track it is necessary to establish the interrelation between duration of a cycle of defectoscopic diagnostics and actual output of defective rails, and also it is required to establish the dependence between number of such defectoscopic diagnostics and actual output of defective rails. The optimum number of defectoscopic diagnostics in a cycle should meet the condition of guaranteed crack detection at the pre-critical stages of its development, ensuring the integrity of the rail before its removal from the track. The following regularities were used to determine the duration of defectoscopic diagnostics cycle Тc for a particular section taking into account [2]. Rails can be in two states at the defectoscopic diagnostics of a section. The first - the defect is not detected due to its absence or insufficient development. The second - the defect is detected. The quantitative measure of finding the rail in these states, i.e. the measure of the situation, is the corresponding probabilities. A.Y. Khinchin proved that probability can be considered as a fraction of time during which the considered state exists [3].